Relation of multi-vessel coronary artery disease to response to aspirin. (25th November 2020) - Shiyovich, A; Sasson, L; Lev, E; Solodky, A; Kornowski, R; Perl, L
Abstract: Background: Multi-vessel coronary artery disease (MV-CAD) is correlated with worse outcomes compared with single-vessel CAD (SV-CAD), potentially attributed to more advanced atherosclerotic disease in other vascular beds, greater endothelial dysfunction, thrombin activation and possibly greater platelet reactivity. Objectives: The aim of the current study was to evaluate the association between MV-CAD and high on-aspirin platelet reactivity (HAPR) in patients with stable CAD treated with aspirin. Methods: Patients with known stable CAD, who were taking aspirin (75–100 mg qd) regularly for at least one month, and had undergone coronary angiography at least 3 months prior to the test, were enrolled. Blood was drawn from the participants and sent for platelet function testing. MV-CAD was defined as >50% stenosis in ≥2 separate major coronary territories per coronary angiography. HAPR was defined as aspirin reaction units (ARU) >550. Results: Overall 507 patients were analyzed; age 66.7±11.2, 17.9% women, 223 (44%) had MV-CAD. Mean ARU was significantly higher among patients with MV-CAD vs. SV-CAD (460±68 vs. 440±55, p<0.001, respectively). Furthermore, the rate of HAPR was significantly higher among patients with MV-CAD (figure 1). In a multivariate analysis adjusted for potential confounders, MV-CAD was found to be a strong independent predictor of HAPR [OR=1.8 (95% CI1.05–4.7), p=0.014]. In a reverse analysis, HAPR was associated with a higher number of coronary vessels involved (1.95±0.65 vs. 1.45±0.57, p<0.01) and a strong independent predictor of MVD (OR-2.44, CI 1.83–25.6, p=0.015). Conclusions: MV-CAD is significantly associated with HAPR. This could potentially explain, in part, the increased risk and/or worse outcomes in patients with MV-CAD and implies considering intensive anti-thrombotic therapy among these patients. Funding Acknowledgement: Type of funding source: None